Disorder of three‐dimensional chromosome structure plays a role in carcinogenesis. Issue 1 (24th November 2021) - Zhang, Linlin; Liu, Fangming; Wu, Lihong; Fu, Suolan; Xing, Leilei; Zhang, Lianghui; Wang, Xiangdong; Wang, Yong‐Xiao
Abstract: The three‐dimensional structure of chromatin is an essential part of gene expression and regulation. Modules far apart in the one‐dimensional DNA sequence can be close to each other in 3D and activated by spatially folding. Normal gene activation requires such long‐distance interactions. However, the formation of faulty structures of chromosomes can lead to disorders of genetic function, such as cancer. With the development of three‐dimensional (3D) capture techniques, chromatin disorders associated with cancer are gaining attention. In this review, we combined several studies on the 3D genome, regulation and progress of gene expression and involvement of 3D chromatin variation in the development of cancer. We will discuss the possibility and potential value of using the 3D genome as a new target in the clinical diagnosis and treatment of cancer. In a word, high‐order chromatin architecture can provide a new perspective for the study of oncogenic alterations. Abstract : Latest development of 3D genome and its role in gene expression Examples of 3D genomes in cancer Potential value of using 3D genome as a new target in clinical diagnosis and treatment of cancer